2009
DOI: 10.1111/j.1600-0560.2009.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant glomus tumor of the palm: a case report

Abstract: The author herein reports on a glomus tumor of the palm. A 71-year-old man consulted our hospital because of a tumor on the left palm. The tumor was deeply seated, and MRI and CT showed a deep cystic tumor adjacent to the bone. An excision of the tumor was therefore performed. Grossly, the tumor was red and partly cystic. The tumor was well defined from the surrounding tissues, and measured 25 × 24 × 22 mm. Microscopically, the tumor consisted of epithelioid perivascular cells (glomus cells) located around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Malignant transformation is extremely rare, but possible (10,11). Folpe et al (15) proposed the following classification criteria for malignant glomus tumors: i) Deep location and a size of >2 cm; ii) presence of atypical mitotic figures; or iii) combination of moderate to high nuclear grade and mitotic activity (5 MFs/50 HPFs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant transformation is extremely rare, but possible (10,11). Folpe et al (15) proposed the following classification criteria for malignant glomus tumors: i) Deep location and a size of >2 cm; ii) presence of atypical mitotic figures; or iii) combination of moderate to high nuclear grade and mitotic activity (5 MFs/50 HPFs).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lesions have been reported in neurofibromatosis-1 (8). Malignant transformation is rarely reported (911). …”
Section: Introductionmentioning
confidence: 99%
“…Terada et al reported a 2.5-cm malignant glomus tumor resected from the palm, which recurred locally and was re-excised. 8 A glomus tumor of the thumb with classic symptoms was reported by Wetherington et al in a 30-year-old woman. 9 Excision revealed a tumor 0.5 cm in size that was thought to be malignant on immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…There are only 6 reports of malignant glomus tumors in the hand-ranging from 5 mm to 4.5 cm in size. 3,[5][6][7][8][9] Re-classification of glomus tumors has suggested that a diagnosis of malignant should be reserved for tumors with a risk of metastasis, which seems to correlate with a deeper location, size greater than 2 cm, atypical mitotic figures equal or greater than 5 mitotic figures per 50 high-power field, and moderate to high nuclear grade. 1 We describe the largest malignant glomus tumor of the hand ever reported.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant GT (MGT) is very rare, and only a few cases have been reported [18][19][20][21][22][23][24][25]. The malignancy of GT is now based on the system proposed by Folpe et al in 2001 [12].…”
Section: Introductionmentioning
confidence: 99%